EP34 Assessing the ability of anti-C1q antibody measurement to predict a flare of lupus nephritis. (20th April 2020) - Bahal, Sameer; Pyne, Dev; Rajakariar, Ravindra; Lewis, Myles; Pakozdi, Angela; Cove-Smith, Andrea
Abstract: Background: Systemic lupus erythematous (SLE) is a multi-system autoimmune disease which has a relapsing and remitting course. Patients with lupus nephritis (LN) are at risk of relapse and hence long term follow up and disease monitoring are of particular importance. Anti-C1q antibodies (C1Q Ab) are observed in 30-60% of patients with SLE. It has been postulated that the presence of C1Q Ab can predict a flare of LN. Here we undertook a prospective follow up of patients after having a C1Q Ab measurement to determine whether the result predicted a flare of LN. Methods: SLE patients attending an Inner-City Lupus Center, were involved in the study. All fulfilled the 2012 SLICC criteria for SLE. A point-in-time measurement of C1Q Ab was made using an ELISA kit (Orgentec Diagnostika GmbH). A positive test defined by the manufacturer is a level above 10 U/ml. Medical records of patients were reviewed over the following 1 year to identify LN flares. A renal flare was defined as a doubling of the protein creatinine ratio with a subsequent decision to escalate immunosuppressive therapy. Chi Squared tests were used to assess statistical significance. 9 patients who were being treated for a flare of LN at the time of C1Q Ab were excluded from the analysis. Results: 116 lupus patients were included in the study. Of those, 52 had biopsy proven LN (45%). Positive C1Q ab was more common in patients with a history of biopsy proven LN (n = 17, 32.7%) compared to those with non-renal SLE (n = 10, 15.6%), (p = 0.03). Renal flares tended to be more common in C1q ab positive LN patients (n = 4, 26.7%) compared to those without C1q ab (n = 2, 7.14%). (p = 0.782). Of the 64 patients with non-renal SLE, 1 (10%) C1Q Ab positive patient subsequently developed LN compared with 1 (1.85%) C1Q Ab negative patient (p = 0.173).There was no correlation between the level of C1Q Ab and the rate of LN flares. Having a positive dsDNA antibody level at the time of sampling also did not appear to predict a flare. Conclusion: C1Q Ab has a known correlation with LN, however its ability to predict flares has been less well characterised. Our prospective analysis shows that although the C1Q Ab positive patients were more likely to have a flare of LN in the following year, there was not a statistically significant difference between the C1Q Ab positive and negative groups. In addition, only a relatively small proportion of C1Q Ab positive patients went on to have a flare (20%). Our data therefore does not support the use of C1Q Ab as a predicting factor for a subsequent flare of LN. Disclosures: S. Bahal None. D. Pyne None. R. Rajakariar None. M. Lewis None. A. Pakozdi None. A. Cove-Smith None.